Higher AVCO2 and Lactate Gradient Combined with SOFA Score as a Mortality Predictor during the 6-Hours of Resuscitation of Septic Shock - Morteza Talebi Doluee; Sahar Azam Ghasemzadeh; Ahmad Bagheri Moghadam; Zahra Abbasishaye; Davood Soroosh; Elnaz Vafadar Moradi (Archives of Anesthesia and Critical Care)
Background: Sepsis is a severe and life-threatening condition leading to widespread inflammation and organ dysfunction. It is a medical emergency that requires immediate attention and treatment. One of the key indicators used to assess the severity and prognosis of sepsis is lactate level. Another key indicator of sepsis severity is a significant difference in the level of carbon dioxide (CO2) between veins and arteries. Methods: In this study, we aimed to evaluate the differences in the venous and arterial PCO2 and lactate levels during the first 6 hours of treatment of septic shock. In this prospective observational-analytical study patients with septic shock admitted to the ICU were evaluated. Sepsis is defined as patients who had 1 or more of the SIRS criteria with a possible or proven source of infection and hypotension despite appropriate fluid therapy who needed to receive vasopressors. Results: Among 85 patients the mean age was 64±17 years and 48 (56%) were men. Of these patients, 15 (17%) died, of them 8 (53.33%) were male, 14 (93%) were diabetic, 11(73.33%) were hypertensive, 11 (73.33%) had ischemic Heart disease and 9 (60%) patients had Chronic Obstructive Pulmonary Disease (COPD). The mean HR, SBP, and DBP were significantly higher in lived patients; the SOFA scores were significantly lower in these patients. Conclusion: Overall, the gradient of AV PCO2 and lactate clearance combined with SOFA score can be a valuable tool for clinicians in predicting mortality risk in critically ill patients and guiding treatment decisions.